2020
DOI: 10.1128/msphere.00183-20
|View full text |Cite
|
Sign up to set email alerts
|

Secretion of Recombinant Interleukin-22 by Engineered Lactobacillus reuteri Reduces Fatty Liver Disease in a Mouse Model of Diet-Induced Obesity

Abstract: The incidence of metabolic syndrome continues to rise globally. In mice, intravenous administration of interleukin-22 (IL-22) ameliorates various disease phenotypes associated with diet-induced metabolic syndrome. In patients, oral treatment is favored over intravenous treatment, but methodologies to deliver IL-22 via the oral route are nonexistent. The goal of this study was to assess to what extent engineered Lactobacillus reuteri secreting IL-22 could ameliorate nonalcoholic fatty liver disease. We used a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 25 publications
0
18
0
Order By: Relevance
“…In general, the majority of these studies have addressed the effects of specific probiotic strains in animals challenged by diets leading to NAFLD. In this line, the administration of several probiotic strains (mainly Lactobacillus and Bifidobacterium ) has been shown to be effective in reducing liver lipid accumulation under dietary conditions providing 40 to 65% of energy as fat [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ]. Moreover, this effect is also maintained when excessive hepatic lipid accumulation is mediated by dietary conditions providing high sugar intakes (10 to 30% of energy as fructose).…”
Section: Effects Of Probiotic Administration (Single Strain and Mixtu...mentioning
confidence: 99%
“…In general, the majority of these studies have addressed the effects of specific probiotic strains in animals challenged by diets leading to NAFLD. In this line, the administration of several probiotic strains (mainly Lactobacillus and Bifidobacterium ) has been shown to be effective in reducing liver lipid accumulation under dietary conditions providing 40 to 65% of energy as fat [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ]. Moreover, this effect is also maintained when excessive hepatic lipid accumulation is mediated by dietary conditions providing high sugar intakes (10 to 30% of energy as fructose).…”
Section: Effects Of Probiotic Administration (Single Strain and Mixtu...mentioning
confidence: 99%
“…paracasei F19 can provide the enzyme N -acyl-phosphatidylethanolamine-preferring phospholipase D, which indirectly produces a natural lipid, palmitoylethanolamide, playing a role in regulating inflammation [ 250 ]. Moreover, through modulating the intestinal microbiota and reducing bacterial translocation to the liver, IL-22-expressing Limosilactobacillus reuteri has been reported to alleviate ethanol-induced steatohepatitis [ 247 ] and reduce nonalcoholic fatty liver diseases [ 246 ]. These constructed probiotics exert a powerful anti-inflammatory capacity, especially shown in the hepatic and intestinal axis.…”
Section: Modified Probiotics and Diseasesmentioning
confidence: 99%
“…Besides, some studies have revealed the potential use of engineered bacteria (e.g., Lactobacillus reuteri producing IL-22) to restore homeostasis to the gut-liver axis. 157,158 Other approach under study is to directly target the microbiota either with antibiotics, currently nonspecific and with potential side effects, or with bacteriophages, viruses that can defeat specific species of bacteria. Another approach that has gained attention lately is the supplementation with microbe-derived products (so-called postbiotics) to replace metabolic activities lost due to dysbiosis.…”
Section: Final Remarks and Future Prospectsmentioning
confidence: 99%